Numerical Investigation of Laterally Loaded Piles in Clayey Soils - Tzivakos, Konstantinos (Σχολή Πολιτικών Μηχανικών, 2017)
The p-y curve method is a very common engineering practice for the calculation of the internal forces and deformations along laterally loaded piles under lateral loading (bending moments, shear forces, horizontal displacements, etc.). The pile is simulated as a “Beam on a Non-linear Winkler Foundation” (BNWF) while the p-y curves control the distributed load-horizontal displacement relationship of the non-linear springs. The soil springs are considered fixed on one end and connected with the pile-beam on the other. If one succeeds in calibrating accurately these springs regarding their strength and stiffness, the aforementioned calculations become reliable and representative of the actual lateral pile response. The major condition for the realistic simulation of the problem through the specific method is the significant density of the soil springs along the pile. The doctoral thesis indicates certain divergence between the existing p-y curves of the literature for soft, normally consolidated (NC) and stiff, overconsolidated (OC) clayey soils under undrained loading conditions. Subsequently, a sophisticated three-dimensional finite element model is designed in the code Simulia Abaqus (coupled analyses, pile-soil interface, advanced constitutive simulation of the soil), for the parametric investigation of the lateral pile response in the aforementioned soil types. In more detail, the parametric analyses output formulates numerical p-y curves for various soil, pile and interface properties, while the numerical model as well as the proposed curves are validated through comparisons with experimental results found in the literature. The original contribution of the thesis consists in: • The development of a sophisticated, three-dimensional numerical model for the performance of coupled effective stress and hydraulic flow analyses, aiming to simulate the lateral loading of a single pile in clayey soils. • The incorporation of a complex constitutive law for the soil simulation (small-strain stiffness, structure degradation) and realistic modelling of the pile-soil interface. • The highlighting of additional soil mechanics parameters affecting significantly the p-y curves, which are not taken into account by the existing methodologies (slope of the normal compression line λ and the unloading-reloading lines κ, Poisson’s ratio v and the ratio of the residual to the peak undrained shear strength RF). • Proposal of new p-y curves for soft, normally consolidated clayey soils, which are valid for a wide range of soil and pile parameters, taking into account the aforementioned effects. • Proposal of new p-y curves for stiff, overconsolidated clayey soils, which are valid for a wide range of soil and pile parameters, taking into account the aforementioned effects. • Investigation of the effect of cyclic loading on the post-cyclic response of the pile and the individual characteristics of the respective post-cyclic p-y curves.